EFL Students' Difficulties in Applying Lexical Inferencing Strategies in Reading Authentic Literary Texts - Muhammad Syafrizal Amrul; Intan Permata Hapsari (IKIP PGRI Bojonegoro, 2026)
While lexical inferencing helps EFL learners deduce words, it frequently fails with authentic literature due to figurative language and cultural nuances. This qualitative study investigated the inferencing difficulties of English Education students reading familiar and unfamiliar literary texts. Data from five purposively selected students were gathered via task-based questionnaires and interviews, then analyzed using Miles et al.'s (2018) interactive model and Nassaji's (2003) taxonomy. Results showed that despite using various strategies, students consistently encountered failures. They often fell for false lexical anchors caused by polysemy and rarely self-corrected. Furthermore, strong storyline engagement led to